2016
DOI: 10.1371/journal.pone.0168541
|View full text |Cite
|
Sign up to set email alerts
|

Dexrazoxane Shows No Protective Effect in the Acute Phase of Reperfusion during Myocardial Infarction in Pigs

Abstract: Calcium and iron overload participate in the mechanisms of ischemia/reperfusion (I/R) injury during myocardial infarction (MI). Calcium overload induces cardiomyocyte death by hypercontraction, while iron catalyses generation of reactive oxygen species (ROS). We therefore hypothesized that dexrazoxane, an intracellular metal chelator, would attenuate I/R injury. MI was induced in pigs by occlusion of the left anterior descending artery for 1 hour followed by 2 hours reperfusion. Thirty minutes before reperfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Similarly, other well-recognized ferroptosis inhibitors, such as Fer-1 [ 59 ], DFO [ 63 ] and dexrazoxane (DXZ) [ 64 ], have been shown to provide effective protection against MIRI by attenuating ferroptosis. However, it should be noted that even some common ferroptosis inhibitors, such as DXZ, an intracellular metal chelator, have previously been reported to have no protective effect on MIRI in pigs [ 148 ]. Thus, the different pharmacodynamics, bioavailability and subcellular localization of ferroptosis inhibitors should be considered in future studies on I/R injuries.…”
Section: Therapeutic Strategies Targeting Ferroptosis In I/r Injurymentioning
confidence: 99%
“…Similarly, other well-recognized ferroptosis inhibitors, such as Fer-1 [ 59 ], DFO [ 63 ] and dexrazoxane (DXZ) [ 64 ], have been shown to provide effective protection against MIRI by attenuating ferroptosis. However, it should be noted that even some common ferroptosis inhibitors, such as DXZ, an intracellular metal chelator, have previously been reported to have no protective effect on MIRI in pigs [ 148 ]. Thus, the different pharmacodynamics, bioavailability and subcellular localization of ferroptosis inhibitors should be considered in future studies on I/R injuries.…”
Section: Therapeutic Strategies Targeting Ferroptosis In I/r Injurymentioning
confidence: 99%
“…Chelation therapy using EDTA (ethylene diamine tetraacetic acid) with acute MI patients showed attenuated adverse cardiovascular outcomes [103]. Dexrazoxane, a mitochondria-permeable intracellular metal chelator, also decreased free radicals and improved the ex vivo hemodynamics of I/R injuries in rat hearts [104], while showing no protective effect on I/R injuries in pigs [105]. Further studies could take advantage of the different bioavailibilities, pharmacodynamics, and subcellular localization of chelators to select the right chelator in combination with other therapies that target the effect of iron in cardiovascular disease.…”
Section: Drugs and Therapies Targeting Iron And Myocardial Ischemia-rmentioning
confidence: 99%
“…However, several clinical and animal studies have found that, when low tissue perfusion after ischemia is addressed, not only does ischemic tissue damage fail to resolve but also the injury is aggravated. [ 2 8 ] This phenomenon, first described by Jennings et al [ 9 ] in 1960, is defined as ischemic reperfusion injury (IRI). Myocardial IRI is often found in patients undergoing procedures involving ischemia reperfusion such as percutaneous coronary intervention (PCI), thrombolysis, coronary artery bypass grafting (CABG), and valve replacement, and its primary clinical manifestations are ventricular arrhythmia, lack of reflow phenomenon, and distal embolization.…”
Section: Introductionmentioning
confidence: 99%